Skull vibration-induced nystagmus test in unilateral superior canal dehiscence and otosclerosis: a vestibular Weber test. (June 2014) - Dumas, Georges; Lion, Alexis; Karkas, Alexandre; Perrin, Philippe; Perottino, Flavio; Schmerber, Sébastien
Abstract Conclusions: The skull vibration-induced nystagmus test (SVINT) acts as a vestibular Weber test and reveals a vibration-induced nystagmus (VIN), elicited mainly on the vertex location, with a horizontal or torsional component beating more often toward the side of the lesion in superior canal dehiscence (SCD) than in otosclerosis (OS). In SCD, the VIN vertical component is most often up-beating. These results suggest more a global vestibular contribution than the sole stimulation of the superior semicircular canal. Objectives: This study aimed to evaluate the possible occurrence of nystagmus during SVINT in unilateral conductive hearing loss related to SCD or OS. Methods: The slow-phase velocities (SPVs) of the VIN horizontal, torsional, and vertical components were recorded in patients with a unilateral otologic lesion (17 SCD, 38 OS) and 12 control subjects. Vibratory stimulations (60 Hz, 100 Hz) were applied on the vertex and on each mastoid. Results: In SCD, VIN was observed in 82% of patients with a primarily torsional, horizontal, and vertical (up-beating) component in 40%, 30%, and 30%, respectively. Horizontal and torsional components beat toward the side of the lesion more often than in OS. Higher SPVs were observed after vertex stimulation. In OS, VIN was sparse with low amplitude and was not systematically lateralized to a specific side.